Advances in Service-Oriented and Cloud Computing : Workshops of ESOCC 2016, Vienna, Austria, September 5–7, 2016, Revised Selected Papers /: Workshops of ESOCC 2016, Vienna, Austria, September 5–7, 2016, Revised Selected Papers. (2018) - Unknown
No abstract available